2012
DOI: 10.1038/cdd.2012.148
|View full text |Cite
|
Sign up to set email alerts
|

A role for c-FLIPL in the regulation of apoptosis, autophagy, and necroptosis in T lymphocytes

Abstract: Caspase 8 plays a dual role in the survival of T lymphocytes. Although active caspase 8 mediates apoptosis upon death receptor signaling, the loss of caspase 8 activity leads to receptor-interacting protein (RIP)-1/RIP-3-dependent necrotic cell death (necroptosis) upon TCR activation. The anti-apoptotic protein c-FLIP (cellular caspase 8 (FLICE)-like inhibitory protein) suppresses death receptor-induced caspase 8 activation. Moreover, recent findings suggest that c-FLIP is also involved in inhibiting necroptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 41 publications
1
66
0
Order By: Relevance
“…21 Other forms of cell death were unaffected. 22,23 Previous studies have observed an important contribution of programmed necrosis in Alfp-and Mx1-Cre transgenic models, which was not observed to the same extent herein and likely reflect differences in the different animal models used. 10 The onset of liver injury was preceded by increasing concentrations of inflammatory cytokines/chemokines including IL-6, IFN-γ, TNF and CCL2 in serum.…”
Section: Discussionmentioning
confidence: 38%
“…21 Other forms of cell death were unaffected. 22,23 Previous studies have observed an important contribution of programmed necrosis in Alfp-and Mx1-Cre transgenic models, which was not observed to the same extent herein and likely reflect differences in the different animal models used. 10 The onset of liver injury was preceded by increasing concentrations of inflammatory cytokines/chemokines including IL-6, IFN-γ, TNF and CCL2 in serum.…”
Section: Discussionmentioning
confidence: 38%
“…During rapid growth, such as that experienced by T cells after antigenic stimulation, T cells switch their energy metabolism from favoring oxidative phosphorylation (TCA cycle) to aerobic glycolysis (43), a process that can be enhanced by IL-15 signaling through CD122 (44). Cells that are stuck favoring the TCA cycle and unable to meet increased energy demands are more likely to die from necroptosis (45). Necroptosis is another form of programmed cell death often mediated by the protein kinases RIPK1 and RIPK3 (46,47) and enhanced by the presence of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…66 Caspase 8 has also been shown to repress necrosis by processing CYLD. 67 Interestingly, caspase 8 appears to act in a proteolytically active complex with FADD and cFLIP to block RIP1-and RIP3-mediated necrosis, 65,68 with c-FLIP- 69 and FADD-70,71 deficient cells being highly sensitive to death by necrosis. This is consistent with the developmental lethality, due to cardiac failure, in FADDdeficient embryos, 72 with RIP1 deficiency rescuing the embryonic lethality associated with FADD deficiency.…”
Section: Rip1 and Rip3 As Drivers Of Necroptosismentioning
confidence: 99%